2024
DOI: 10.1017/s0029665124000028
|View full text |Cite
|
Sign up to set email alerts
|

Reframing interventions for optimal child nutrition and childhood obesity: the importance of considering psychological factors

Lisa Newson,
Julie Abayomi

Abstract: This review aims to emphasise the impact of poor nutrition on children’s health and psychological wellbeing, urging those involved in childhood obesity or nutrition services to broaden their intervention approach. Poor nutrition and childhood obesity affect physical and psychological health. The stress of living with obesity further impacts quality of life, wellbeing and self-esteem. Children living with obesity may experience adverse childhood events and stress, and young people are able to recall the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
1
0
Order By: Relevance
“…These include childhood stress and the negative effects of low self-esteem on emotions, mental health and eating behaviours, which are associated with weight discrimination and stigma (19) . A more holistic approach, that addresses psychosocial and emotional needs, may positively influence engagement with and long-term sustainability of health behaviour change interventions (19,20) .…”
Section: Nutrition In Childhoodmentioning
confidence: 99%
“…These include childhood stress and the negative effects of low self-esteem on emotions, mental health and eating behaviours, which are associated with weight discrimination and stigma (19) . A more holistic approach, that addresses psychosocial and emotional needs, may positively influence engagement with and long-term sustainability of health behaviour change interventions (19,20) .…”
Section: Nutrition In Childhoodmentioning
confidence: 99%
“…Noteworthy, however, that only 20% of the studies systematically reported psychosocial outcomes, with the most common being quality of life, and only 5% of the studies recorded mental health outcomes (such as depression). 16 Despite the relationship between obesity and psychological variables and the increased risk of psychological comorbidities in individuals living with obesity, 20 there is a lack of attention given to psychological variables as part of obesity treatment, 21 especially within UK guidelines. 22 , 23 , 24 This lack of focus on psychological variables is partly due to insufficient research on interventions that systematically assess psychological factors.…”
Section: Introductionmentioning
confidence: 99%